BUGIS LOCAL WISDOM IN SHORT STORIES AS ENFORCEMENT OF LITERATURE TEACHING MATERIALS IN JUNIOR HIGH SCHOOL - Juanda Juanda (Prosiding Seminar Nasional dan Internasional HISKI, 2023)
Local wisdom is the values passed down by ancestors to the next generation from generation to generation for the preservation of culture in a place. However, the reality is that in the current era, the millennial generation is less concerned about preserving ancestral culture, especially Bugis' local wisdom. The purpose of this study was to explore the values of local wisdom of the Bugis tribe in the short stories Fajar  News Paper  published online  in Makassar and their relevance to the enrichment of teaching materials in junior high schools. This study uses a qualitative-interpretative method. The data in this study are words, phrases, clauses, and sentences in short stories that represent local wisdom in the Bugis tribe. The data source is a short story published by Fajar  News Paper in Makassar on the web ruangsastra.com. July 2020 to January 2021 period by Dul Abdul Rahman. Determination of short story text is done by purposive sampling is a technique of determining short stories with certain criteria (Sugiyono, 2008). There are two short stories chosen in this study, namely the short story  “Fish in the River’s Bajoe" ‘Ikan Sungai Bajoe’ Fajar 26 July 2020 and "The Crazy People and Saga Source Water Sacred" ‘Orang Gila dan Hikayat Mata Air keramat’ Fajar 24 January 2021. The data analysis technique used the Nvivo12Plus application. This study found the educational value of local wisdom and environmental awareness related to forest conservation. The short story “Fish in the River’s Bajoe" has local wisdom values, namely: maintenance of trees around riverbanks, maintenance of river ecosystems, religion (Puang Sandro as ritual leader); The short story The Crazy People and Hikayat Source Water Sacred" has local wisdom: forest conservation (sacred forest ‘appanorengge’), belief that forests are a source of water, religion (Puang Sandro as ritual leader), and taboo. These two short stories can be used as enrichment of teaching materials in the 2013 curriculum KD 3.5 and 4.5 and 3.6 and 4.6. learning short stories in grade IX junior high school.